Bio-ionic Liquids as Adjuvants for Sulfonylurea Herbicides. Issue 3 (20th March 2018) - Marcinkowska, Katarzyna; Praczyk, Tadeusz; Łęgosz, Bartosz; Biedziak, Agnieszka; Pernak, Juliusz
Abstract: Five bio-ionic liquids (BILs) with choline cations and fatty acid anions derived from pelargonic acid, glycerol tristearate, glycerol trioleate, canola oil, and coconut oil were synthesized and applied as spray adjuvants with three sulfonylurea herbicides: metsulfuron-methyl, iodosulfuron-methyl-sodium, and tribenuron-methyl. Physicochemical properties, including thermal stability, solubility, and surface activity, were determined, and the influence of these BILs on herbicidal efficacy was studied in greenhouse tests using four target weed species: common lambsquarters ( Chenopodium album L.), cornflower ( Centaurea cyanus L.), corn poppy ( Papaver rhoeas L.), and oilseed rape ( Brassica napus L.). BILs, particularly those with the oleic anion and anions derived from canola oil and coconut oil, greatly improved herbicidal activity. Addition of BILs to the spray solution significantly reduced the surface tension and contact angle of spray droplets and increased the area of herbicide deposit on the leaf surface.